A new era for optic pathway glioma: A developmental brain tumor with life-long health consequences - Walker, David A.; Aquilina, Kristian; Spoudeas, Helen; Pilotto, Chiara; Gan, Hoong-Wei; Meijer, Lisethe (Frontiers in Pediatrics, 2023)
Optic pathway and hypothalamic glioma (OPHG) grow slowly and present with clinical features driven by their precise anatomical site within the optic pathways and hypothalamus, their age at presentation and the stage of growth and development of the host neural and orbital bony tissues. Up to 50% arise in association with Neurofibromatosis type 1 (NF1) . They almost never transform to malignant glioma and rarely threaten life. They do threaten vision loss, can cause diencephalic syndrome in infancy and hypopituitarism later in life as well as progressive cognitive and behavioural dysfunction. Long term endocrine deficits strongly influence the need for lifelong health care of the majority of children who will survive. The past two decades has seen an expansion in our understanding and knowledge of the clinical and scientific features of these tumours, their modes of presentation, the need for careful visual assessment and decision-making surrounding clinical management with surgery, radiotherapy, chemotherapy and most recently the potential benefit of molecularly targeted drug therapy. The neuro-oncology multi-disciplinary team concerned with their care has expanded to include ophthalmologists and endocrinologists which means that selection of treatment or observation requires consideration of visual and endocrine outcomes as well as anatomical, surgical, histology, biomarker and imaging criteria. This article is based upon the authors’ clinical and research experience, as well as the published literature. It highlights advances in approach to diagnosis, anatomical classification of tumours with respect to vision loss, endocrine and neurological consequences and their influences on case selection for therapy or observation. The history of different treatment approaches will be described and the standards of practice specified by consensus groups and current trial protocols will form the basis for recommendation for case selection for treatments that are currently available and under trial. It concludes with suggestions for avenues of research and service development directed at improving long term outcomes and support the majority of children who survive into adulthood